A Big Battle: The State vs. Indigenous People (Case Study in Jambi Province) - M. Yusuf; Syafrial Syafrial (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The change in designation of Bukit Duabelas area into Bukit Duabelas National Park in Jambi province raises a conflict between the national park official who was ruling the zonation system in the national park and the Orang Rimba people who have lived there for many years. The decision of the protected area aims to preserve the life and culture of Orang Rimba. However, zoning rules in the field are interpreted as an effort to limit space and access to the forest resources for Orang Rimba who have traditionally utilized them. This research uses a case study approach to explore the dynamics of conflict on the protected area. The results of the study show that conflicts in national park management are very dynamic because of shifting disagreement about the protection area. The conflicts began with debates about the zoning system which led into the fight for access to the park resources which were contested over the concept of national parks and customary forests. This paper argues the battle over the national park was not only about contested natural resources but also was a fight for authority and power between the state and indigenous people over the concept of park management.